2018
DOI: 10.1007/s40789-018-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent mining and reclamation for underground coal mining subsidence impacts in China

Abstract: Large scale underground mining of coal resources in China using longwall mining has resulted in ecological and environment problems, including surface subsidence that is considered serious due to competing interests of prime agricultural lands, food security, and regional economic development. The subsided lands must be rehabilitated soon after mining to be agriculturally productive to minimize loss of farmland. Similarly, precious water resources must also be managed during and after mining to protect this na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…By studying the vertical movement of the surface, one of the relevant questions to be answered is the extent of the zone of influence, e.g., the angle of draw (Cai et al 2016). The latter clearly is different from one coal basin to another, and it is influenced by the geological conditions (Peng 1986;Wagner and Schümann 1991;Galvin 2016;Chugh 2018). Second, one of the reasons that most research focuses on either the immediate impact of longwall mining or the impact over a period of a few years is that most research addresses a specific problem or question.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…By studying the vertical movement of the surface, one of the relevant questions to be answered is the extent of the zone of influence, e.g., the angle of draw (Cai et al 2016). The latter clearly is different from one coal basin to another, and it is influenced by the geological conditions (Peng 1986;Wagner and Schümann 1991;Galvin 2016;Chugh 2018). Second, one of the reasons that most research focuses on either the immediate impact of longwall mining or the impact over a period of a few years is that most research addresses a specific problem or question.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Subsidence and accumulated water disasters have become the primary ecological environment problems faced by coal mine subsidence areas with high phreatic levels. Village flooding, farmland damage, and disruptive changes in the ecosystem have brought great challenges to the construction of ecological civilization in the mining area [14,15], and these are the urgent problems in the coal mining areas that need to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the numbers of closed mines and those which are planned to be set up, it may be concluded that even with the rapid development of new mining projects, most workers will stay unemployed. At the same time, post-mining underground space, in most cases, has not been considered as a suitable place for activities other than mining and are often filled with rocks and water to prevent its further effect on the local environment [17][18][19]. In general, widely considered methods of underground mines reclamation aim to utilize the most cost-effective and efficient way of backfilling to prevent further ground subsidence after mine closure [20].…”
Section: Introductionmentioning
confidence: 99%